Correlation of the interleukin-29 levels in crevicular fluid and plasma with the genetic polymorphism in chronic and aggressive periodontitis patients. Issue 1 (January 2015) - Shivaprasad, B.M.; Pradeep, A.R.
Highlights IL-29 levels were increased in GCF and plasma of periodontitis patients. IL-29 has a role in pathogenesis of periodontitis and can act as a biomarker for periodontitis. rs30461 SNP is not related to susceptibility to periodontitis in this population of Indian individuals.